Structural reforms and growth in transition: A meta-analysis - Jan Babecký; Tomáš Havránek (Charles University in Prague, Institute of Economic Studies (IES), 2013)
The present fiscal difficulties of many countries amplify the call for structural reforms. To provide stylized facts on how reforms worked in the past, we quantitatively review 60 studies estimating the relation between reforms and growth. These studies examine structural reforms carried out in 26 transition countries around the world. Our results show that an average reform caused substantial costs in the short run, but had strong positive effects on long-run growth. Reforms focused on external liberalization proved to be more beneficial than others in both the short and long run. The findings hold even after correction for publication bias and misspecifications present in some primary studies.
Keywords: C83; O11; P21; 330; Structural reforms; growth; transition economies; meta-analysis; Bayesian model averaging